Heterogeneity in Callous-Unemotional Traits: Early Temperamental and Environmental Risk Factors in a High-Risk Sample - Kristin J. Perry; Jamie M. Ostrov; Stephanie T. Lanza; Amanda B. Nickerson; Pamela Schuetze; Stephanie A. Godleski; Rina D. Eiden (Clinical Psychological Science, 2026)
The Sensitivity to Threat and Affiliative Reward model posits that low levels of threat sensitivity and affiliative reward predict callous-unemotional (CU) traits. In a prospective sample ( N = 161; 73% Black or multiracial; 46.0% male) with prenatal substance exposure, we characterized heterogeneity in maternal and early adolescent ( M = 13.26 years, SD = 0.88) reports of CU traits using latent profile analysis. A three-profile solution was selected: low maternal/average youth rating (26.40%), moderate risk (52.11%), and high risk (21.49%). The high-risk profile demonstrated the highest levels of late adolescent ( M = 15.08 years, SD = 0.83) aggression. Regarding temperament and early childhood environmental risk (1–60 months) predictors, the moderate-risk profile had the highest levels of toddlerhood fear. At high child responsiveness, higher violence exposure was associated with greater odds of high- or moderate-risk profile membership, aligned with a secondary pathway to CU traits. There was also some support for a primary temperament pathway to youth-reported CU traits.